A Pendampingan Pembuatan Media Pembelajaran Terbarukan Berbasis Metaverse Bagi Guru Sekolah Dasar: Pendampingan Pembuatan Media Pembelajaran Terbarukan Berbasis Metaverse Bagi Guru Sekolah Dasar - Suciptaningsih, Oktaviani Adhi; Yulianti, Yulianti; Fajariyanto, Otto; Yuniawatika, Yuniawatika; Rahayu, Winanjar; Divina, Amina (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Curriculum changes have a psychological and physical impact on the Indonesian learning community, especially for teachers in adapting to the challenges of digital technology in their learning which has become an era for students today. The aim of the Community Service (PKM) activity is to assist Purwodadi 4 State Elementary School teachers, Malang City, in developing metaverse-based learning media. The problems faced by partners of SDN Purwodadi 04 Malang are 1). Low knowledge and innovation of teachers in developing digital-based learning media that attracts students' learning interest, 2). Teachers' skills are low in innovating digital learning by integrating local wisdom. The activity methods used to achieve PKM goals include assistance in creating metaverse-based renewable learning media. Results of activities after training and mentoring: 1). Teachers' knowledge is increasing about the nature of the metaverse in learning, 2). Increasing teacher skills in innovating metaverse-based renewable learning by utilizing learning media, suggestions for further service so that the learning media we design is adapted to students' learning needs using the Teaching at The Right Level (TaRL) approach.